324 Neurosurgical Cost Containment Via Improved Physician Awareness. (1st August 2016) - Agarwal, Nitin; Agarwal, Prateek; Mazurkiewicz, Anna; Wecht, Daniel A.; Friedlander, Robert M.
Abstract: INTRODUCTION: Several studies in the literature have demonstrated that physicians are often unaware of prescription drug, laboratory, diagnostic, and surgical supply costs. Other studies have suggested that increased physician awareness of supply cost contributes to reduced overall cost. In this study, we investigated the effects of such increased awareness on neurosurgical cost containment. METHODS: Within the Department of Neurological Surgery at the University of Pittsburgh Medical Center, physicians were informed of the prices of various ventricular shunt brands, such as the more expensive Medtronic shunts vs the more economic fixed Integra shunt. In addition, the costs of DuraGen vs alternative materials used during craniotomy such as Gelfoam were reviewed with faculty neurosurgeons. RESULTS: The total supply cost of ventricular shunts in fiscal year 2015 was 383 026 and the estimated total supply cost of shunts in fiscal year 2016, based on fiscal year 2015 volume, was 273 553. Supply costs of ventricular shunts decreased from 1916 per procedure in fiscal year 2015 to 1375 per procedure in fiscal year 2016. The total supply cost of DuraGen in fiscal year 2015 was 344 689 and the estimated total supply cost of DuraGen in fiscal year 2016, based on fiscal year 2015 volume, was 195 021. Supply costs of DuraGen decreased from 279 per procedure in fiscal year 2015 to 159 per procedure in fiscal year 2016. CONCLUSION: Physician awareness of surgical supply costs within our department of neurosurgery successfully resulted in significant cost savings.